Facial attractiveness and CEO compensation : Evidence from the banking industry - Ahmed, Shaker; Ranta, Mikko; Vähämaa, Emilia; Vähämaa, Sami (Elsevier, 2023)
This paper examines the effect of facial attractiveness on the compensation of bank Chief Executive Officers (CEOs). Consistent with the so-called beauty premium hypothesis, we document that good looks pay off for bank CEOs. Specifically, by utilizing machine learning to assess the facial appearance of the CEOs of large U.S. banks, we find that CEO facial attractiveness is positively associated with the annual total compensation and the discretionary, performance-based components of compensation. The total compensation of above-average looking bank CEOs is about 24% higher than the compensation of CEOs with below-average looks after controlling for various CEO-specific and bank-specific attributes that are known to affect executive compensation. Furthermore, our results indicate that facial attractiveness is weakly positively related to the annual base salary while being unrelated to the pay-performance and pay-risk sensitivities of bank CEO compensation. Overall, our empirical findings provide strong evidence for the existence of a beauty premium in the executive labor market.
Keywords: Facial attractiveness; CEO compensation; Beauty premium; Bank CEOs; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|